KEPEMIMPINAN DAN KINERJA PEGAWAI SUATU STUDI PADA KANTOR SEKRETARIAT DAERAH KOTA DENPASAR - I Gusti Gde Oka Pradnyana; Anggreni Widia Ningsih (Forum Manajemen STIMI Handayani Denpasar, 2013)
Human factors arethe main functionswithin eachactivity. Allactions takenmust be initiated by the human members of the organization. Denpasar DistrictSecretariat ofﬁ ceis one of the functions of Government Agencies organizationofcommunity serviceto be onefocus of attention in performance improvement. One keyfactor to increase or decrease the performance of employees is the role of a leaderwhois able to provide motivation for employees.The purposeof this studyto determineand analyze the patterns of leadership and employee performance.In this study data collection through questionnaires proportional random sampling with a sample size of 57 employees, and analyzed using simple correlation analysis,signiﬁ cant test, simple regression analysis anddetermination, with using programSPSS16.0 For Windows, based on the resultsof research and discussion suggeststhat there relationships and inﬂ uences are very strong andsigniﬁ cant relationshipbetween leadership variablesonthe variable performance of employees in the Ofﬁ ceof the Regional Secretariat of Denpasar.